Hands Up! Atypical Defensive Reactions in Heavy Players of Violent Video Games When Exposed to Gun-Attack Pictures - Santos, Maria Fernanda; Bastos, Aline F.; Oliveira, Jose M.; Figueira, Ivan; Gleiser, Sonia; Pereira, Mirtes G.; Volchan, Eliane; Erthal, Fátima S. (Frontiers in Psychology, 2019)
Threatening cues and surrounding contexts trigger specific defensive response patterns. Posturography, a technique for measuring postural strategies, has been used to evaluate motor defensive reactions in humans. When exposed to gun pointed pictures, humans were shown to exhibit an immobility reaction. Short and long-term exposure to violent video games was shown to be a causal risk factor for increased violent and aggressive behavior. Assaultive violence with a gun is a major trigger for motor defensive reactions, and post-traumatic stress disorder (PTSD) is the most characteristic psychiatric sequelae. Recent studies point to links between PTSD symptoms and emotional shortfalls in non-clinical trauma-exposed samples. The present study investigated defensive reactions to gun threat and PTSD symptoms in heavy players of violent video games compared to non-players. Male university students were screened according to use of violent video games and divided in three groups: non-players, moderate players, and heavy players. Stimuli were pictures depicting a man pointing a gun directed at the participant. In matched control pictures, non-lethal objects replaced the gun. Posturography was recorded and PTSD symptoms were assessed. When exposed to the threat pictures, non-players exhibited the expected reduction in amplitude of body sway (immobility), heavy players presented atypical augmented amplitude of body sway, and moderate players showed intermediate reactivity. Heavy players presented a significant distinct reaction compared to non-players. They also scored significantly higher in PTSD symptoms than non-players. Disadvantageous defensive reactions and higher vulnerability to PTSD symptoms, revealed in the present study, add to other shortcomings for heavy players.